The influence of areas of worklife fit and work‐life interference on burnout and turnover intentions among new graduate nurses. (30th June 2015) - Boamah, Sheila A.; Laschinger, Heather
Abstract : Aim: To examine the relationships among the overall person‐job match in the six areas of worklife, work‐life interference, new nurses' experiences of burnout and intentions to leave their jobs. Background: As a large cohort of nurses approaches retirement, it is important to understand the aspects of the nurses work‐life that are related to turnover among new graduate nurses to address the nursing workforce shortage. Methods: Secondary analysis of data collected in a cross‐sectional survey of 215 registered nurses working in Ontario acute hospitals was conducted using structural equation modelling. Results: The fit indices suggested a reasonably adequate fit of the data to the hypothesised model [ χ 2  = 247, d.f. = 122, P  = 0.001, χ 2 /d.f. = 2.32, Incremental Fit Index (IFI) = 0.954, Comparative Fit Index (CFI) = 0.953, Root Mean Square Error of Approximation (RMSEA) = 0.06]. Person‐job match in six areas of worklife had a direct negative effect on burnout (emotional exhaustion and cynicism), which in turn had a direct positive effect on turnover intentions. Work‐life interference also influenced turnover intentions indirectly through burnout. Conclusion: The study findings demonstrate that new graduate nurses' turnover intentions are a recurring problem, which could be reduced by improving nurses' working conditions. Retention of new graduate nurses could be enhanced by creating supportive working environments to reduce the susceptibility to workplace burnout, and ultimately, lower turnover intentions. Implications for Nursing Management: Managers must employ strategies to enhance workplace conditions that promote a person‐job fit and work‐life balance to improve retention of new graduate nurses, and, thereby, lessen the nursing shortage.